Immune checkpoint inhibitor-related Stevens-Johnson syndrome and toxic epidermal necrolysis: a retrospective analysis of 21 cases - Pu, Tianshu; Teng, Yaru; Zhang, Yuezhu; Da, Meihong; Wang, Fei (Frontiers in Immunology, 2026)
IntroductionStevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare but life-threatening severe cutaneous adverse reactions (SCARs) increasingly linked to immune checkpoint inhibitors (ICIs).MethodsWe retrospectively analyzed 21 patients with ICI-related SJS/TEN treated at Zhongda Hospital, Southeast University, from 2019 to 2025.ResultsThe median latency from ICI initiation to onset was 28 days, most commonly following PD-1 inhibitors such as sintilimab and tislelizumab. Patients presented with diffuse erythema, blistering, erosions, and frequent mucosal involvement. All discontinued ICIs and received systemic corticosteroids; some additionally received intravenous immunoglobulin (IVIG). The mean time to re-epithelialization was about 10 days, and mortality reached 14.3%, limited to TEN cases.ConclusionICI-related SJS/TEN, though rare, represents a serious immune-related adverse event that requires prompt recognition and early immunosuppressive therapy. Increased awareness and further studies are needed to clarify its mechanisms and guide management. Based on our findings, we recommend heightened vigilance for early mucocutaneous symptoms in patients receiving ICIs, prompt dermatology referral for suspected cases, and establishment of standardized reporting pathways to national pharmacovigilance systems to ensure rapid identification and pooled analysis of ICI-related SJS/TEN cases.